Упростите выражение : (p\q+q\p)^2 - (p\q - q\p)^2 -2

juliettehasagun juliettehasagun    1   07.09.2021 15:02    0

Ответы
РумакСтепан РумакСтепан  25.11.2021 08:24

Применим формулу разности квадратов  a^2-b^2=(a-b)(a+b).

   (\frac{p}{q} +\frac{q}{p} )^2-(\frac{p}{q} -\frac{q}{p} )^2-2=              

=(\frac{p}{q} +\frac{q}{p} -\frac{p}{q} +\frac{q}{p} )(\frac{p}{q} +\frac{q}{p} +\frac{p}{q} -\frac{q}{p} )-2=

=2\frac{q}{p} *2\frac{p}{q} -2=

=4*\frac{q}{p} *\frac{p}{q} -2=

=4-2=2

ответ:   2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика